Effects of Caffeine Consumption on Blood Glucose Regulation: A Systematic Review - Paulus Damar Bayu Murti; James Ngginak; Windy Rizkaprilisa (Science Technology and Management Journal, 2026)
Caffeine, a principal constituent of coffee and other beverages, has been extensively examined for its influence on metabolism, including its effect on glycemic control. This systematic review synthesizes the current evidence on the impact of caffeine on blood glucose levels in both healthy individuals and those with diabetes. The review examines the underlying mechanisms, including the reduction in insulin sensitivity and the stimulation of catecholamine release that result from caffeine consumption, which ultimately lead to a transient increase in blood glucose levels. Furthermore, the review addresses the acute and chronic effects of caffeine, emphasizing the dose-dependent nature of its impact. Although acute caffeine intake has been linked to impaired glucose tolerance and elevated blood glucose levels, habitual coffee consumption has been associated with a reduced risk of Type 2 diabetes. This suggests that other bioactive compounds in coffee may counteract the negative effects of caffeine. Nevertheless, for individuals with Type 1 and Type 2 diabetes, caffeine's potential to exacerbate glycemic control remains a concern. This review highlights the necessity for further research to elucidate the long-term consequences of caffeine consumption on glucose metabolism, particularly in diabetic populations, and to provide guidance for the safe consumption of caffeine.